Perundungan Siswa Reguler Terhadap Siswa Anak Berkebutuhan Khusus di Sekolah Dasar Negeri Taman Cibodas Kota Tangerang - Cellotara Situmorang; Denti Kardeti; Eri Susanto (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2026)
This study explores bullying by regular students against students with special needs at Taman Cibodas State Elementary School, Tangerang City. The aims is to describe the forms of bullying, analyze the causes, and propose a program to prevent bullying and strengthen inclusive interaction. Using a qualitative method, data were collected through interviews with students with special needs, regular students, teachers, and parents. The results show that students with special needs experience verbal bullying (name-calling), physical bullying (hitting), and relational bullying (exclusion). Factors include perceptions that inclusive students are different (way of speaking, slow learning, being quiet), peers seeing teasing as jokes, imitation of others, lack of understanding of how to interact with inclusive students, and the tendency of some inclusive students to withdraw. To address this, the TEMAN BAIK is recommend, consisting of Sekolah Ramah Kata (a one-time awareness session for all students) and Buddy Time (weekly peer buddy activities). This program is expected to build empathy, reduce bullying, and create a safer, more inclusive school environment that supports the social and emotional development of students with special needs.